2021
DOI: 10.1002/btpr.3182
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal potential of cell wall degrading enzymes from Trichoderma asperellum against Aedes aegypti (Diptera: Culicidae)

Abstract: Aedes aegypti is a mosquito vector of arboviruses such as dengue, chikungunya, zika and yellow fever that cause important public health diseases. The incidence and gravity of these diseases justifies the search for effective measures to reduce the presence of this vector in the environment. Bioinsecticides are an effective alternative method for insect control, with added ecological benefits such as biodegradability. The current study demonstrates that a chitinolytic enzyme complex produced by the fungus Trich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…are being successfully used and commercialized to combat a wide range of soil phytopathogenic fungi, such as Fusarium oxysporum , Rhizoctonia solani , Sclerotium rolfsii , S. cepivorum , and Alternaria alternate ( Rabinal and Bhat, 2020 ; Godara and Singh, 2021 ; Khalil et al, 2021 ; Álvarez-García et al, 2022 ). The mechanisms of Trichoderma -based plant disease biocontrol include their capacity for nutrient and space competition, parasitism, secretion of antimicrobial metabolites ( Cubilla-Ríos et al, 2019 ; da Silveira et al, 2021 ; Kamaruzzaman et al, 2021 ), activation of defense responses, and promotion of plant growth ( Zehra et al, 2017 ; Chen et al, 2021 ). Among these approaches, the application of VOCs is considered a promising biocontrol strategy for the management of plant diseases, particularly soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…are being successfully used and commercialized to combat a wide range of soil phytopathogenic fungi, such as Fusarium oxysporum , Rhizoctonia solani , Sclerotium rolfsii , S. cepivorum , and Alternaria alternate ( Rabinal and Bhat, 2020 ; Godara and Singh, 2021 ; Khalil et al, 2021 ; Álvarez-García et al, 2022 ). The mechanisms of Trichoderma -based plant disease biocontrol include their capacity for nutrient and space competition, parasitism, secretion of antimicrobial metabolites ( Cubilla-Ríos et al, 2019 ; da Silveira et al, 2021 ; Kamaruzzaman et al, 2021 ), activation of defense responses, and promotion of plant growth ( Zehra et al, 2017 ; Chen et al, 2021 ). Among these approaches, the application of VOCs is considered a promising biocontrol strategy for the management of plant diseases, particularly soil-borne diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Trichoderma asperellum has also been implicated as an anopheline larvicide [ 85 ], and cell-wall-degrading extracts from the fungus have shown larvicidal activity against Ae. aegypti [ 86 ]. Our data highlight the potential diversity and importance of examining enzootic infections in target insect species that can lead to the discovery of novel pathogens that may have important impacts in natural insect populations as well as serve as resources or reservoirs for the isolation of potential (mosquito) biological control agents.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the capacity of the fungal hyphae to penetrate into the larval body was ascribed to the secretion of proteases and chitinases, which collaborated in the destabilization of the insect cuticle 48 . To the best of our knowledge, only one study has directly correlated the insecticidal activity of T. asperellum to the production of chitinases, demonstrating that a chitinolytic complex produced by T. asperellum ENZT00 was effective in disrupting cuticle formation in Aedes aegypti larvae 49 …”
Section: Discussionmentioning
confidence: 99%
“…48 To the best of our knowledge, only one study has directly correlated the insecticidal activity of T. asperellum to the production of chitinases, demonstrating that a chitinolytic complex produced by T. asperellum ENZT00 was effective in disrupting cuticle formation in Aedes aegypti larvae. 49 In this study, we investigated the production of chitinases by T. asperellum ICC012 in different cultivation conditions and tested their effects, via oral administration, on the development and survival of two lepidopteran species, the reference model B. mori, and S. littoralis, one of the most destructive agricultural pests in tropical and subtropical areas. 50 We previously reported that oral administration of a fermentation-derived commercial preparation of chitinases from T. viride, containing a mixture of different chitinases (with endo-and exo-chitinase, as well as ⊎-N-acetylglucosaminidase activities), was able to impair the growth of B. mori larvae by destroying the integrity of their peritrophic matrix.…”
Section: Discussionmentioning
confidence: 99%